Deadly Weapons Concealed, Etc., & Shooting Firearms, Ch. 30, § 185, in Revised Ordinances City of Sarcoxie, Jasper County, MO (1907). - (:unkn) unknown (General Publisher, 1907)
. No person in this city shall discharge any gun, pistol or other fire arms, or explode any detonating material, and any person so offending shall be deemed guilty of a misdemeanor, but this section shall not apply to any officer in the discharge of his duty nor to the operator or workman in any mine, nor to persons properly using any lawful target gun in any licensed shooting gallery."
--
Keywords: DISCHARGE